2013
DOI: 10.1016/j.talanta.2013.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Mercury compounds characterization by thermal desorption

Abstract: The ability to accurately determine metal mercury content and identify different mercury species in solid samples is essential for developing remediation and control strategies. The aim of the present study is to characterize mercury compounds based on thermal desorption. For this purpose a series of samples was prepared and the operational parameters-heating velocity, carrier gas-were optimized. Fifteen commercial mercury compounds were analyzed for use as fingerprints. The results of the study show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
147
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 28 publications
19
147
2
Order By: Relevance
“…One of the most promising of these methods is based on the selective thermal desorption of mercury species from the solid sample, referred to in this work as HgTPD. This method has already been employed to identify the mercury composition of soils, sediments, airborne particulate matter and FGD gypsum among others [17][18][19][20][21]. Nevertheless, it still needs to be validated and the scientific community has yet to demonstrate that the method is reproducible for any solid matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most promising of these methods is based on the selective thermal desorption of mercury species from the solid sample, referred to in this work as HgTPD. This method has already been employed to identify the mercury composition of soils, sediments, airborne particulate matter and FGD gypsum among others [17][18][19][20][21]. Nevertheless, it still needs to be validated and the scientific community has yet to demonstrate that the method is reproducible for any solid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, in this work, a thermal desorption procedure that was performed using a previously optimised and validated device [20], was employed to identify mercury species WFGD gypsum samples obtained from both industrial processes and laboratory tests under different operational conditions. The aim was to assess the scope of the method for identifying mercury species in WFGD gypsums and its capacity to predict the fate of mercury in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…When the reference compounds were prepared using the same matrix of the samples studied (fly ash, gypsum and soil), the high-peak temperatures obtained were similar. Possible interferences or interactions during the thermal release of the different mercury species were discarded when several Hg compound mixtures were analysed [14]. The tests for speciation of mercury in the different matrices were carried out in HgTPD-1 in the case of fly ash, gypsum and soil samples and in HgTPD-3 for fly ash and gypsum.…”
Section: Reference Mercury Compoundsmentioning
confidence: 99%
“…A promising technique with low detection limits is that based on thermal programmed desorption (HgTPD) [12][13][14]. Moreover, HgTPD is an easily accessible technique which can be implemented without the need for complicated instrumentation or for the time-consuming sample pre-treatment required by EXAFS and SCE.…”
mentioning
confidence: 99%
“…Hg p is easily removed by dust control equipment, such as electrostatic precipitator (ESP) or bag house filters. Lopez-Anton et al [13,14] demonstrated that HgCl 2 , HgS, HgO, and HgSO 4 were the main Hg species in coal-fired ash. Due to the diverse thermal stabilities of different mercury species, the mercury speciation can be identified via analyzing their thermal stabilities.…”
Section: Introductionmentioning
confidence: 99%